2022
DOI: 10.3389/fmed.2022.870330
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Optical Quality After SMILE, Wavefront-Optimized LASIK and Topography-Guided LASIK for Myopia and Myopic Astigmatism

Abstract: PurposeTo compare visual outcomes and corneal optical quality after small incision lenticule extraction (SMILE), wavefront-optimized (WFO) FS-LASIK, and topography-guided customized ablation treatment (TCAT) FS-LASIK for myopia.MethodsThis prospective case-series study included 283 eyes of 283 myopic patients who underwent SMILE or FS-LASIK. There were 102, 100, and 81 eyes in the SMILE group, WFO group and TCAT group, respectively. The tomography system (Sirius) was used to measure corneal aberrations and opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We evaluated the already identified literature and found 4 new articles from their reference sections and cited articles. Ultimately, 19 articles that satisfied our criteria were included in this meta-analysis (7,8,(10)(11)(12)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Figure 1 displays a flow chart of the literature reviewed in this study.…”
Section: Results Of the Screening And Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the already identified literature and found 4 new articles from their reference sections and cited articles. Ultimately, 19 articles that satisfied our criteria were included in this meta-analysis (7,8,(10)(11)(12)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Figure 1 displays a flow chart of the literature reviewed in this study.…”
Section: Results Of the Screening And Sensitivity Analysismentioning
confidence: 99%
“…The prior occurrence of HOA was eradicated and the development of new HOA was avoided ( 9 ). Despite the technical advantages, there is very conflicting data on whether personalized corneal refractive surgery results in decreased postoperative induction of HOA compared to SMILE procedures ( 10 ). Kwak et al ( 11 ) discovered that SMILE does not cause spherical aberration (SA) in several types of HOA.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, both groups had excellent safety profiles, with no significant differences. Kang and Zhang et al similarly found no safety differences between TG-LASIK and SMILE, with over 90% of eyes in both groups experiencing no change or improvement in lines of CDVA 6 months postoperatively [ 4 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In response to this rise, many advancements in excimer laser platforms have been made to make these procedures more accurate, effective, and safer for patients [ 2 ]. WaveLight® Contoura Vision topography-guided LASIK (TG-LASIK), approved by the US Food and Drug Administration (FDA) in 2016, utilizes preoperative corneal topography measurements in its excimer laser platform to create a customized ablation to maintain the aspheric corneal shape and minimize surgically induced corneal irregularities [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation